Loan Loss Provision Behaviours in Mainland China Commercial Banks from year 2011-2016 - Meng, Haoyun (2017)
This paper adopts an unbalanced panel database of 193 Chinese commercial banks during 2011-2016 to investigate loan loss provision behaviours in Chinese banking. Because we considered the lag effect, a two-step GMM approach is used to avoid the endogeneity problem. By viewing the literature, we proposed the income smoothing hypothesis, business cycle hypothesis and capital management hypothesis. Following Bryce et al. (2015)’s research, we also test for X-efficiency hypothesis doubt that bad management has an impact on banks’ loan loss provision behaviour. SFA was applied to test X-efficiency scores, the mean score of cost efficiency in Mainland China is around 85 percent. We have found income smoothing behaviour and capital management behaviour in the sample Chinese banking during the sample year. But we did not find specify evidence for business cycle and X-efficiency behaviours. The empirical results are mixed, potential reason are given and some implications are given as well.